Research on Bolt-Grouting Reinforcement Technology for Deep Soft Rock Roadways - Zhang, Zhiliu (International Journal of Natural Resources and Environmental Studies, 2025)
With the continuous development of coal mining into deeper strata in China, the effective support of deep soft rock roadways has become one of the key challenges restricting safe and efficient mine production. In response to the complex engineering conditions of the deep soft rock at the 140505 working face of Kouzidong Coal Mine, a non-uniform bolting-grouting support technology was adopted, which combines conventional bolting and grouting reinforcement with additional strengthening at the shoulder zones. Numerical simulation results demonstrate that after the implementation of the bolting-grouting support, the maximum roof subsidence was reduced from 762 mm to 242 mm, and the floor heave decreased from 404 mm to 106 mm, indicating effective control of the surrounding rock deformation. This approach provides a reliable guarantee for safe and efficient mine production.